Trophic Structure of Neuston Across Tropical and Subtropical Oceanic Provinces Assessed With Stable Isotopes - Albuquerque, Rui; Bode, Antonio; González-Gordillo, Juan Ignacio; Duarte, Carlos M.; Queiroga, Henrique (Frontiers in Marine Science, 2021)
The marine neuston, organisms living in the vicinity of the ocean surface, is one of the least studied zooplankton groups. Neuston occupies a restricted ecological niche and is affected by a wide range of endo- and exogenous processes, while also being a food source to zooplankton, fish migrating from the deep layers and seabirds. In this study, the neustonic communities were characterized along the Malaspina global expedition sampling tropical and subtropical oceanic provinces using stable carbon and nitrogen isotopes to explore their trophic structure and relationships with environmental variables. The differences in stable isotopes mirrored the patterns in environmental characteristics of each province. High δ13C values were associated with atmospheric carbon inputs, while the presence of dinoflagellates, coccolithophorids and upwelling influence are related to low δ13C values. Similarly, provinces presenting high δ15N values were associated with denitrification and nitrate diffusive fluxes, whereas the presence of low δ15N is attributable to nitrogen supplied through N2 fixation by diazotrophs. Neuston showed a large overlap among the isotopic niches of four functional groups, with chaetognaths and detritivores generally exhibiting a smaller degree of overlap compared to carnivores and omnivores/herbivores. These results support the hypothesis of a common trophic structure in the neuston community across the ocean. However, the size of the niche, small in coastal areas and those influenced by upwelling and large in oligotrophic regions, and their overlap, low in more productive provinces and high in oligotrophic provinces, may be associated with food availability. Small trophic niches are associated with a dominance of specialized over-opportunistic feeding in productive environments.